Estudio De Factibilidad Tecnológica Para Implementar Un Sistema Informático De Control Y Monitoreo De Mercadería En El Área De Bodega Del Almacén Montoya Del Cantón Vinces - Burgos Montoya, Germania Johanna (2018)
Currently, businesses are competing to occupy a place in the market, for this they need the different tools that exist to improve and optimize its internal growth, and one of these tools is the use of technology. The "Montoya" warehouse located in Sucre street between Bolívar and Balzar del Cantón Vinces, province of Los Ríos is a family business that started in 1973, dedicated to the sale of fabrics and appliances in general, this business was one of the first warehouses of the Canton, at present maintains its clients and day by day the increase of them. The main problem of the business is the deficiency in the control and monitoring of the merchandise, the constant loss of household appliances, the lack of security of the merchandise that has the highest demand. This is why the warehouse has decided to incorporate the use of technological tools into its business.